EFFECT OF FREQUENCY AND DURATION OF THERMOSONICATION ON THE PHYSICAL, CHEMICAL AND MICROBIOLOGICAL QUALITY OF COW'S MILK - Almira Dinar Dhiny; Jariyah Jariyah; Luqman Agung Wicaksono; Anugerah Dany Priyanto; Serly Safitri; Wildan Naufal Esfandiar (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2023)
Milk is a food product that contains many nutrients. Thermosonication is a method combining ultrasonic and medium-temperature heating that can be used as an alternative pasteurisation method because it can maintain the nutrients contained in milk while providing safety assurance for consumption. This study aimed to determine the effect of frequency and duration of thermosonication on the physical, chemical and microbiological quality of cow's milk. The experimental design used was a completely randomised design (CRD) with two factorials of frequency (20 and 22kHz) and duration of thermosonication (5, 10, 15 and 20 minutes). The data obtained were analysed with ANOVA and BNJ further tests at the 5% level. The best treatment was 22kHz frequency for 20 minutes with the results of viscosity 3.80 ± 0.000 cP, pH 6.8 ± 0.00, fat content 3.22 ± 0.00%, protein content 2.19 ± 0.01% and total bacteria 0.53 ± 0.67 log CFU/ml, and was able to reduce Escherichia coli bacteria by 2.95 log CFU/ml.